Efficacy of Cyanoacrylate Glue Ablation of Primary Truncal Varicose Veins Compared to Existing Endovenous Techniques: A Systematic Review of the Literature - Dimech, Anthony Pio; Cassar, Kevin (The Surgery Journal, 2020)
Introduction One-third of adults in the United States and United Kingdom suffer from varicose veins. n-butyl-2-cyanoacrylate (NBCA) glue is a novel endovascular, nontumescent, nonthermal ablation technique for treatment of this condition. It has proved effective in multiple studies since its first use in 2013. The aim of this systematic review is to assess the efficacy of NBCA in ablating primary truncal varicose veins and eliminating reflux compared with existing endovascular techniques. Secondary outcomes include complications and quality of life.Methods PRISMA was used as a guide and studies were screened for risk of bias and methodological quality. Subjects had to be ≥18 years of age and followed-up posttreatment with color Duplex ultrasound (DUS). Eligibility criteria included saphenofemoral junction (SFJ) or saphenopopliteal junction (SPJ) incompetence with reflux down truncal veins lasting >0.5 seconds on DUS interrogation and a Clinical, Etiological, Anatomical, and Pathophysiological classification of venous disorders ranging between C1 and C6.Results Out of 2,910 patients (3,220 veins) in 17 studies, 1,981 were administered NBCA, 445 radiofrequency ablation (RFA), and 484 endovenous laser ablation (EVLA) with mean procedure times of 25.7, 23.2, and 28.7 minutes, respectively. Mean recruitment period was 9 months (1–36 months) and followed-up for an average of 12.3 months (1–36 months). The majority were C2 to C3. Two-year occlusion rates were 93.7, 90.9, and 91.5% for NBCA, RFA, and EVLA, respectively. NBCA-treated patients experienced the least complications, with bruising, phlebitis, and pain being the most prevalent. Quality of life improved equally in all three modalities.Conclusion NBCA is simple to administer, safe, and effective even without compression stockings. Further studies are required to assess longer-term benefit and the effect of anticoagulation on vein obliteration.
Keywords: n-butyl 2 cyanoacrylate; radiofrequency; laser; saphenous vein; varicose veins